6(6-2x)=156

Simple and best practice solution for 6(6-2x)=156 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(6-2x)=156 equation:


Simplifying
6(6 + -2x) = 156
(6 * 6 + -2x * 6) = 156
(36 + -12x) = 156

Solving
36 + -12x = 156

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + -12x = 156 + -36

Combine like terms: 36 + -36 = 0
0 + -12x = 156 + -36
-12x = 156 + -36

Combine like terms: 156 + -36 = 120
-12x = 120

Divide each side by '-12'.
x = -10

Simplifying
x = -10

See similar equations:

| 7(4x+4)=84 | | 2u+v+2w=-2 | | 7t^2+28t+8=0 | | 3(4x-3)=5(2x+1) | | 7(2x-2)=-112 | | 3m-9=6 | | 3x^4-6x^3-x+2=0 | | (x+3)(x+18)=180 | | 6(3o-0)=-36 | | -6x+10=6x+58 | | ln(x^2)+3lnx-2ln(3x)=lny | | 0-5(d-1.5)=2.5 | | 3-(3x+5)=0 | | 5+3x=6x+14 | | 6x-9=10x+5 | | -8v+1=7v-20 | | (3x+5)-3=0 | | 5+3x=6x+-14 | | 2(15-y)+6y=42 | | 50-2x=40+4x | | 2(6+7x)=166 | | 57=5x+12 | | 5u-3v+4w=-3 | | 16x^2-25x+9216=0 | | (-8.6)+7.2= | | -7.5+-7.6= | | 3u+2v+2w=-1 | | 7e=42 | | 9(l+2)=3(-2) | | 3y-12=-y+6 | | 8+4x=x+2 | | x^4-17x^3+90x^2-108x-216=0 |

Equations solver categories